2016
DOI: 10.1002/ange.201508613
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Elastic Strain on Catalytic Activity in the Hydrogen Evolution Reaction

Abstract: Understanding the role of elastic strain in modifying catalytic reaction rates is crucial for catalyst design, but experimentally,t his effect is often coupled with al igand effect. To isolate the strain effect, we have investigated the influence of externally applied elastic strain on the catalytic activity of metal films in the hydrogen evolution reaction (HER). We showthat elastic strain tunes the catalytic activity in acontrolled and predictable way. Both theory and experiment show strain controls reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 46 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Recently, Yan et al [66,67] demonstrated that mechanical strain in catalysts such as Pt/Ni/Cu thin film on a Ti substrate and WC on a polymeric substrate significantly affects the catalytic activity. We considered the possibility of a similar effect in the catalysts studied in this work, however, such an effect is unlikely, as our catalysts are single-phase metal or alloy nanoparticles dispersed on micro sized particles of an oxide support rather than heterogeneous layers.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Yan et al [66,67] demonstrated that mechanical strain in catalysts such as Pt/Ni/Cu thin film on a Ti substrate and WC on a polymeric substrate significantly affects the catalytic activity. We considered the possibility of a similar effect in the catalysts studied in this work, however, such an effect is unlikely, as our catalysts are single-phase metal or alloy nanoparticles dispersed on micro sized particles of an oxide support rather than heterogeneous layers.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption and dissociation of H 2 on transition metal surfaces has been related to the availability of d-electrons in the band structure of the metals through the d-band centre model [46,47]. It is possible to bring about shifts in the d-band centre through strain effects [48]. However, the close match between the atomic radii of Cu and Ni means that strain effects due to alloying are likely to be minimal and the position of the d-band centre will be largely determined by electronic effects in Cu/Ni alloys.…”
Section: Catalystmentioning
confidence: 99%
“…Previous studies have indicated that tensile strain could upshift the d-band center to intensify the species adsorption (e. g., C=C) to speed up ECH. [12,13] However, tensile strain synchronously enhances PdÀ H bonding which impedes the transfer of H ads and the following hydrogenation activity. Fortunately, alloying of heteroatoms (e. g., Ru, Cu) into Pd lattice can weaken PdÀ H bonding through so-called synergistic effect to promote hydrogenation.…”
Section: Introductionmentioning
confidence: 99%